COMMUNICATIONS IN MANAGEMENT SYSTEMS - N. Efimochkina (Вестник университета, 2018)
In the modern world, information exchange is becoming dominant. Information is one of the main resources in the management system and the eectiveness of communication interactions directly aects the life activity of the organization. The most common form of communication interactions in the management system is documented communication. The documents reect the legitimacy of all interactions and processes, which are implementing in the organization. In the context of rapidly developing computer technologies, communication processes, including through the interchange of documented information, acquire qualitatively new forms. The article reveals the conceptual aspects of modern communication processes, their structure and importance for the management of modern organizations.